Analysis of Microstructure and Mechanical Properties of CoCrMo Alloys Processed by Metal Binder Jetting Multi-Step Technique - Alessandro Pellegrini; Fulvio Lavecchia; Maria Grazia Guerra; Luigi Maria Galantucci (Journal of Manufacturing and Materials Processing)
Metal Binder Jetting (BJT/M) has emerged as a promising additive manufacturing (AM) technology for the realization of complex parts using a wide range of metal alloys. This technology offers several advantages, such as design flexibility, reduced lead times, a high building rate, and the ability to fabricate intricate geometries that are difficult or impossible to achieve with conventional manufacturing methods. Cobalt Chromium Molybdenum (CoCrMo) alloys are particularly suitable for demanding applications in the aerospace, biomedical, and industrial sectors that require high strength and hardness, corrosion resistance, and biocompatibility. In this work, ten cubic and ten tensile samples were printed with a layer height of 50 µm using the shell printing method, debound and sintered at 1325 °C for 4 h, with the aim of investigating the properties of CoCrMo parts made using BJT technology. A density of 7.88 g/cc was obtained from the Archimede’s test. According to the printing and sintering parameters, an average hardness of 18.5 ± 1.8 HRC and an ultimate tensile strength of 520.5 ± 44.6 MPa were obtained. Finally, through a microstructure analysis, an average grain size of 182 ± 14.7 µm was measured and the presence of an intergranular Cr-rich phase and Mo-rich carbides was detected.